2010
DOI: 10.1063/1.3400648
|View full text |Cite
|
Sign up to set email alerts
|

Self-consistent field lattice model study on the phase behavior of physically associating polymer solutions

Abstract: The phase behavior of physically associating polymer solutions, where the polymer chain contains a small fraction of "stickers" regularly placed along the backbone, is studied using self-consistent field lattice model. Two inhomogenous morphologies are observed. One is a microfluctuation homogenous (MFH) morphology, where the mean-field values of the local average concentrations of polymers phi(P)(r) and stickers phi(st)(r) slightly fluctuate around their respective bulk average values phi(P) and phi(st) and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 54 publications
(54 reference statements)
3
26
0
Order By: Relevance
“…Nearest neighbor pairs of stickers have attractive interaction −ǫ with ǫ > 0, which is the only non-bonded interaction in the present system. In this simulation, however, instead of directly using the exact expression of the nearest neighbor interaction for stickers, we introduce a local concentration approximation for the non-bonded interaction similar to the references [23,27]. The interaction energy is expressed as:…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Nearest neighbor pairs of stickers have attractive interaction −ǫ with ǫ > 0, which is the only non-bonded interaction in the present system. In this simulation, however, instead of directly using the exact expression of the nearest neighbor interaction for stickers, we introduce a local concentration approximation for the non-bonded interaction similar to the references [23,27]. The interaction energy is expressed as:…”
Section: Theorymentioning
confidence: 99%
“…When a local concentration approximation for the nonbonded interaction is introduced, the SCFT descriptions of lattice model for PAPSs presented in this work is basically equivalent to that of the "Gaussian thread model" chain for the similar polymer solutions [28]. The related illumination in detail refers to reference [27].…”
Section: )mentioning
confidence: 99%
“…It is shown that the magnitude of the temperature-dependent range of micelle aggregation does not monotonously change withφ P , which is different from the case of changing N st at fixedφ P . 1 The structural morphology of MFH morphology [17] occurs at a narrow region of ∆χ = 0.1 neighboring the micellar boundary whenφ P > 0.7 (not shown), which is ignored.…”
Section: Resultsmentioning
confidence: 99%
“…Although self-intersections of a chain are not permitted, the excluded volume effect is sufficiently taken into account [21]. The saddle point is calculated using the pseudo-dynamical evolution process [17]. The calculation is initiated from appropriately random-chosen fields ω + (r ) and ω − (r ), and stopped when the change of free energy F between two successive iterations is reduced to the needed precision.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation